2020
DOI: 10.1007/s13199-020-00709-5
|View full text |Cite
|
Sign up to set email alerts
|

Amphitropical variation of the algal partners of Pseudephebe (Parmeliaceae, lichenized fungi)

Abstract: Lichens are present in most terrestrial ecosystems on Earth and colonize extreme habitats, where vascular plants are unable to thrive, due to unique properties of the fungal-algal symbiosis. Here, we explored the phylogeographic structure of green algae engaged in symbiosis with species in the genus Pseudephebe (Parmeliaceae). These often form deep brown to blackish fruticose thalli on acidic rocks, and have partially overlapping distributions: P. minuscula is bipolar and co-occurs with P. pubescens in Europe.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 78 publications
2
11
0
Order By: Relevance
“…Of these, only two thalli came from a mountain massif in Spain, while all the other samples were collected on the Italian Alps. Trebouxia belonging to clade “S” and more specifically to the T. simplex and Trebouxia “S02” lineages have already been documented in Alpine lichens ( Blaha et al, 2006 ; Garrido-Benavent et al, 2020 ) and have been previously reported for T. atra as well ( Muggia et al, 2010 , 2014a ). Although not restricted to the Alps, both T. simplex and Trebouxia “S02” have been reported from lichen symbioses from cold and rather humid areas, and our survey seems to confirm once again their ecological preferences.…”
Section: Discussionmentioning
confidence: 72%
“…Of these, only two thalli came from a mountain massif in Spain, while all the other samples were collected on the Italian Alps. Trebouxia belonging to clade “S” and more specifically to the T. simplex and Trebouxia “S02” lineages have already been documented in Alpine lichens ( Blaha et al, 2006 ; Garrido-Benavent et al, 2020 ) and have been previously reported for T. atra as well ( Muggia et al, 2010 , 2014a ). Although not restricted to the Alps, both T. simplex and Trebouxia “S02” have been reported from lichen symbioses from cold and rather humid areas, and our survey seems to confirm once again their ecological preferences.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, the association with a wide range of symbionts, including locally adapted photobiont strains, has been hypothesized as a driver of lichenized fungal evolution [25,26]. Although the photobiont adaptive hypothesis has only been occasionally experimentally tested in lichens [24,27], several studies have shown a strong correlation between the photobiont genotype and the geographical and ecological distribution of the lichen [23,[28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the exception in clade S is Trebouxia sp. S10, which is known to occur also in the Mediterranean ( Sadowska-Deś et al, 2013 ) and the Neotropical climate (Costa Rica— Nelsen and Gargas, 2009 ; Bolivia— Garrido-Benavent et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…To reveal the structure of the Bolivian photobiont pattern, we analyzed its relationship with the lichen genus or family and assessed the comparative effects of climate, altitude, geographical distances, substrate, and habitat type, as well as thallus type, propagation mode, and secondary metabolites composition. Variation partitioning analysis was carried on the ITS database separately for all Bolivian data obtained in this study ( N = 408 and additional four from Garrido-Benavent et al, 2020 ). Additionally, using all Trebouxia sequences available in GenBank, we applied several variation partitioning analyses on different datasets: all available data ( N = 2,880), Clade A ( N = 1,080), Clade C ( N = 347), Clade I ( N = 381), and Clade S ( N = 1,072).…”
Section: Methodsmentioning
confidence: 99%